Collaboration Between Regional Financing Arrangements and the IMF. (Policy Papers; Policy Paper ;, 2017)
The Global Financial Safety Net (GFSN) has expanded considerably since 2008, including in the non-traditional elements of the safety net such as Regional Financing Arrangements (RFAs). The resulting multi-layered structure of the GFSN makes collaboration between its various elements more important than in the past. Specifically, stronger collaboration between the Fund and RFAs would help increase the effective firepower of the GFSN and ensure a timely deployment of resources. The Fund's experience in macroeconomic adjustment and its universal risk pooling would combine with the greater regional knowledge and country ownership brought the RFA. In this way, improved collaboration between the Fund and RFAs, including in co-financing, would significantly reduce the risk of contagion by encouraging countries to seek early assistance from the Fund. This paper is part of a broader set of proposals to fortify the GFSN (IMF, 2017b, c, d). It proposes both modalities for collaboration-across capacity development, surveillance, and lending-and some operational principles to help guide future co-lending between the Fund and the various RFAs. To date, the only operational guidance to facilitate collaboration has been limited to the high-level 2011 G20 Principles for Cooperation between the IMF and RFAs. Building on several case studies and the principles derived from them, this paper proposes an operational framework for future engagement. It aims to start a more structured dialogue between the Fund and individual RFAs on the modalities of how best to work together.